The paths of history - Diakonov, Igor Mikhailovich (Cambridge, U.K. : New York : Cambridge University Press, 1999)
"The Paths of History provides an overview of the entire history of humanity and the laws governing it. This study takes as its point of departure Marx's theory of social evolution. Igor M. Diakonoff has expanded Marx's five stages of development to eight. In addition, and in contrast to Marx, Diakonoff denies that our transition from one stage to the next is marked by social conflict and revolution and demonstrates that these transitions are sometimes achieved peacefully and gracefully. Professor Diakonoff's focus is not limited solely to the economic and socio-economic aspects of our development; rather he examines in detail the ethnic, cultural, religious and military-technological factors which have been brought to bear over the centuries. He also denies that social evolution necessarily implies progress and shows how 'each progress is simultaneously a regress'. Finally the book concludes with a prognosis for the future of humanity."--BOOK JACKET.
Foreword / Geoffrey Hosking -- 1. First Phase (Primitive) -- 2. Second Phase (Primitive Communal) -- 3. Third Phase (Early Antiquity) -- 4. Fourth Phase (Imperial Antiquity) -- 5. Fifth Phase (the Middle Ages) -- 6. Sixth Phase (the Stable Absolutist Post-Medieval Phase) -- 7. Seventh Phase (Capitalist) -- 8. Eighth Phase (Post-Capitalist).
Includes bibliographical references and index.
Keywords: History -- Philosophy; History -- Periodization; Historiography